1978
DOI: 10.1093/jaoac/61.6.1424
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Liquid Chromatographic Determination of Theobromine and Caffeine in Cocoa and Chocolate Products

Abstract: A method was developed for determining theobromine and caffeine in cocoa and chocolate products by high pressure liquid chromatography. After a simple hot water extraction, both theobromine and caffeine were separated by using a reverse phase Cl s column and a mobile phase of methanol-water-acetic acid (20+ 79+1). Theobromine and caffeine were quantitated at 280 nm; average recoveries were 98.7 and 95.0%; and coefficients of variation were 2.31 and 3.91%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Concentrations of theobromine and caffeine were determined using a modified version of the HPLC method described by Kreiser and Martin 23. A mobile phase of water/acetonitrile (80:20, vol/vol) at a flow rate of 1 mL min −1 and UV detection at 254 nm were applied.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Concentrations of theobromine and caffeine were determined using a modified version of the HPLC method described by Kreiser and Martin 23. A mobile phase of water/acetonitrile (80:20, vol/vol) at a flow rate of 1 mL min −1 and UV detection at 254 nm were applied.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Alkaloids were extracted and analyzed using HPLC as described by Kreiser and Martin (1978), Theobromine and caffeine were identified using known standards, and quantified with the inclusion of theophylline as an internal standard.…”
Section: Analysis Of Lipids Anthocyanin and Alkaloidsmentioning
confidence: 99%
“…Aflatoxins were assayed according to the technique described by Hurst and Toomey (1978). Caffeine was analyzed by the method of Kreiser and Martin (1978).…”
Section: Assaysmentioning
confidence: 99%
“…They hypothesized that the varying levels of aflatoxin produced on three cocoa bean varieties were the result of varying levels of caffeine. Kreiser and Martin (1978) reported that cocoa beans from different geographic origins have varying levels of caffeine. The objective of this study was to examine the aflatoxin production by A. parasiticus on cocoa beans having a wide range of caffeine content.…”
Section: Introductionmentioning
confidence: 99%